Exploring the benefits of Aloe Vera in the cosmetics industry - Simões , Deise Vimaana Santos de Souza; Freitas, João Fábio de; Correia, Mariana de Jesus (Seven Editora, 2024)
This literature review article examines the use of Aloe Vera in the cosmetics industry, highlighting its benefits and properties. Aloe Vera, also known as aloe vera, is a plant widely recognized for its moisturizing, healing, anti-inflammatory, and antioxidant properties. Based on scientific studies and research, this article explores the application of Aloe Vera in beauty products, covering topics such as skin hydration, regeneration, acne treatment, sunburn relief, hair conditioning, and aging prevention. Important considerations when using Aloe Vera in cosmetic formulations are also discussed. Aloe Vera continues to play a vital role in the cosmetics industry by offering natural skin and hair care solutions. DOI:https://doi.org/10.56238/sevened2024.007-083